Applying Policy Process Theories to Environmental Governance Research: Themes and New Directions. (23rd April 2019) - Ruseva, Tatyana; Foster, Megan; Arnold, Gwen; Siddiki, Saba; York, Abigail; Pudney, Riley; Chen, Ziqiao
Abstract : Policy scholars have effectively leveraged policy process models, theories, and frameworks to respond to a variety of important environmental questions. For example, how do environmental issues arrive on the agendas of policymakers? What factors contribute to environmental policy change? What are the designs and effects of institutions (e.g., policies or cultural norms) on environmental governance? In this review, we survey the field of policy process scholarship, focusing on environmental governance, with three objectives. The first objective is to catalog the policy process models, theories, and frameworks most often featured in studies of environmental governance. The second is to capture the methodological choices commonly employed in the application of these models, theories, and frameworks in environmental domains. The third is to identify how these approaches deal with issues central to environmental governance research, including time, space, and policy scale. We aim to identify trends and strategies for integrating key considerations of scale into empirical policy process scholarship.